Evaluation on the Policy of Using the E-Learning System with Fully Online in the Pandemic-Covid-19 Period - Nofri Hendri; Darmansyah Darmansyah (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
The use of e-learning platforms during the Covid-19 pandemic and in the context of facing the era of the industrial revolution 4.0 is a must in almost all levels of education, especially in universities. Many efforts have been made and implemented in order to apply these demands, for example by developing applications that are expected to help organize the digital learning process. The method used in obtaining information is a quantitative method using an instrument, namely a questionnaire (distribution of questionnaires) through the Google form application. The subjects in this study were UNP students in the Fundamentals of Education course in the July-December 2020 semester. Based on the research results, information was obtained regarding the policy evaluation of the use of a full online (online) e-learning system that could be categorized as good and effective, but it needs to be improved in several parts, for example: effectiveness, content, interaction patterns, understanding of the material, network access, large/expensive data packets when using video conference collaborating with the platform e-learning. The element of effectiveness/efficiency of online learning as many as 23.5% of respondents considered it less effective / efficient, meaning that there were still gaps in the fully online policy implemented by universities in this case, namely UNP.